2019
DOI: 10.2147/ndt.s190689
|View full text |Cite
|
Sign up to set email alerts
|

<p>The effect of night shift on sleep quality and depressive symptoms among Chinese nurses</p>

Abstract: PurposeNight shift is associated with adverse physical and psychological health outcomes such as poor sleep quality and depressive symptoms. We aimed to compare sleep quality as well as depressive symptoms in nurses working night shifts to those working day shifts only and explore the association between sleep quality and depressive symptoms among nurses.Patients and methodsEight hundred sixty-five nurses were enrolled in the current study. Sleep quality and depressive symptoms among nurses were evaluated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 46 publications
9
42
1
8
Order By: Relevance
“…The relationship between risk for depression and sleep disturbance in our study was consistent with a study of Norwegian nurses, which indicated that depression was related to sleep problems (Bjorvatn et al, ). Among Chinese nurses, poor sleep quality and working night shift were related to depression (Dai et al, ). Depression and sleep duration had a bidirectional relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between risk for depression and sleep disturbance in our study was consistent with a study of Norwegian nurses, which indicated that depression was related to sleep problems (Bjorvatn et al, ). Among Chinese nurses, poor sleep quality and working night shift were related to depression (Dai et al, ). Depression and sleep duration had a bidirectional relationship.…”
Section: Discussionmentioning
confidence: 99%
“…7 A recent study revealed that 40.8% of nurses exhibited depressive symptoms among 865 Chinese nurses. 10 The depressive symptoms are more likely to occur among nurses than among the general population, which have become the major public health issues in most developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al [11] observed a statistically significant relationship (p < 0.05) between sleep disorders and a shift work system. In the study conducted by Booker's team [12], 20-30% of the individuals working at night suffered from excessive drowsiness during a day combined with sleep disorders.…”
Section: Discussionmentioning
confidence: 96%
“…A rotating day/night shift work system puts strain on the body and disturbs the functioning of defense mechanisms. Exposure to negative factors may contribute to a higher incidence of health problems [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation